2017
DOI: 10.1002/2211-5463.12197
|View full text |Cite
|
Sign up to set email alerts
|

miR‐127‐5p negatively regulates enterovirus 71 replication by directly targeting SCARB2

Abstract: Enterovirus 71 ( EV 71) is the major causative agent of hand‐foot‐and‐mouth disease in young children and can cause severe cerebral and pulmonary complications and even fatality. This study aimed at elucidating whether and how EV 71 infection is regulated by a cellular micro RNA , miR‐127‐5p. We found that miR‐127‐5p can downregulate the expression of SCARB 2, a main receptor of EV 71, by targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Moreover, Wang et al suggested that circulating miR-876-5p was elevated in response to EV71 infections (Wang et al, 2016). Feng et al reported that miR-127-5p can negatively regulate the replication of enterovirus 71 via targeting SCARB2 (Feng et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Wang et al suggested that circulating miR-876-5p was elevated in response to EV71 infections (Wang et al, 2016). Feng et al reported that miR-127-5p can negatively regulate the replication of enterovirus 71 via targeting SCARB2 (Feng et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Directly, miR-127-5p targets the SCARB2 mRNA 3’ untranslated region (UTR) and suppresses expression of SCARB2 in Gaucher fibroblasts ( Siebert et al., 2014 ). Through further experiments, Feng et al confirmed that miR-127-5p expression was upregulated after EV71 infection and that upregulation of miR-127-5p downregulated SCARB2 levels on cell surfaces through specific target binding, which principally affected the susceptibility of uninfected cells to EV71 infection and cell tropism of EV71 ( Feng C. et al., 2017 ). Jin et al found that downregulation of hsa-miR-3605-5p might advance tSCARB2 expression in human embryonic kidney 293T cells infected with coxsackievirus A16 (CVA16), thereby increasing susceptibility to EV71/CVA16 ( Jin et al., 2017 ).…”
Section: Role Of Mirnas In Ev71-induced Cns Infectionmentioning
confidence: 99%
“…The overexpression of miRNA-2911 encoded by Honeysuckle reduced EVA71 replication by directly targeting the VP1-coding sequence [ 48 ]. Loss of function of scavenger receptor class B member (SCARB2), a receptor for EVA71 entry, was caused by miR-127-5p, which led to a decrease in viral replication [ 49 ]. Most dysregulated miRNAs during EVA71 infection can interact with host signaling pathways, indirectly affecting virus replication [ 50 , 51 , 52 ].…”
Section: Known Impacts Of Ncrnas On Ev Replicationmentioning
confidence: 99%